Nocardia farcinica as a cause of chronic meningitis – case report - Moniuszko-Malinowska, Anna (BMC Infect Dis, 2020)
BACKGROUND: Nocardiosis is an uncommon disease caused by aerobic gram-positive bacteria Nocardia spp. Although it is usually an opportunistic infection affecting immunocompromised patients, even one third of cases occur in immunocompetent persons. The aim of the study was to describe the course of chronic meningitis due to Nocardia infection. CASE PRESENTATION: A 52-year-old patient, chalk miner, suffered from a chronic meningitis caused by an extremely rare pathogen. The patient’s history was complicated and diagnostic process covered multiple examinations and consultations. Initially Kocuria rosea was cultured, yet after molecular examination the result was verified to Nocardia farcinica. Targeted antibiotic treatment was implemented, which resulted in gradual improvement of patients condition. A full recovery was achieved after one year antibiotic therapy. CONCLUSIONS: 1. Nocardia farcinica is an uncommon but possible cause of chronic meningitis. 2. In the case of a chronic meningitis of unknown origin multiple cerebrospinal fluid cultures should be performed as the identification of pathogen may be crucial for patient’s recovery. 3. In case of unusual culture, such as Kocuria spp. PCR should be performed.